Looking Back : Raton Band of 1894 (Raton, NM Raton Range, 1978)
Under Picture reads : The Raton Band of 1894 had a lot of brass including a now obsolete two-belled baritone horn carried by a gentleman with a wide-brimmed hat who stood near the drummer for this photo. From left are Jack Hooper, Frank Akers, ? Cosner, Floyd from the Mesa, Arthur Harvey, Albert Shaw, Frank Red, Ed Gray, Dick Butler, Harry Rhoades, Wiley Butler, H. G. Falkerburger, and Frank Falkenburger. This photo was loaned to the range's "Looking Back" series by R. P. Anderson.
Newspaper article + Photograph of the Raton Band of 1894
Mater List Item # 19
File location is in the Raton File Cabinet
Keywords: Hooper, Jack; Akers, Frank; Cosner, ?; Floyd from the Mesa; Harvey, Arthur; Shaw, Albert; Red, Frank; Gay, Ed; Butler, Dick; Rhoades, Harry; Butler, Wiley; Falkenburger, H. G; Falkenburger, Frank; Raton Band; Local Bands; Local Music; Music Groups; Raton, New Mexico